Hemangioma pada Anak: Literatur Review - Arviansyah, Arviansyah; Wihastyoko, Herman; Agustina, Wilma; Siswanto, Yudi; Sintaningrum, Elisabeth (RSUD Dr. Saiful Anwar Province of East Java, 2024)
Hemangioma is a vascular anomaly that is benign and generally occurs in children. ISVVA 2018 classifies vascular anomalies into two categories, namely vascular malformations and vascular tumors (hemangioma). The prevalence of hemangioma is higher in low birth weight babies, premature babies, and girls. Several theories suggest that hemangiomas are caused by vasculogenesis and angiogenesis or an imbalance between angiogenic and antiangiogenic factors. Hemangiomas grow through a proliferation phase, involution phase, and post-involution phase. Hemangioma classification is based on the depth of the lesion, time of appearance of the lesion, distribution of the lesion, and its relationship to syndrome complication.. Diagnosis of hemangioma is based on anamnesis, physical examination, and supporting examinations which include USG, MRI, and CT-Scan. Hemangiomas that lead to complications should require immediate treatment. Hemangioma treatment can be done with topical therapy, systemic therapy (propranolol, corticosteroids, β-blockers, vincristine, rapamycin), laser therapy (PDL, diode, Nd: YAG, argon, KTP, CO2, IPL), and other treatments consisting of from surgical and non-surgical procedures (bleomycin injection).